Effects of pesticides on mango leaf and flower microflora - Lim , Tong Kwee; Khor, Hung Teik (Eugen Ulmer GmbH, 1982)
The ecological effects of a pesticide-foliar fertilizer mixture used for integrated control of mango anthracnose [Colletotrichum gloeosporioides] on the epiphytic microflora were studied. Developing leaves and flowers from sprayed and unsprayed trees were weekly and randomly sampled. Spraying enhanced the saprophytic component of the microflora population but reduced the population of fungal pathogens on both leaves and flowers. This trend was more enduring on the leaves than on the flowers. Leaves had a more diverse microflora than flowers but the overall population decreased with leaf maturity. Flowers had greater numbers of microorganisms which increased further as the flower aged. Results of dilution plating were compared with direct tissue plating.